Does size matter? A test of size‐specific mortality in Atlantic salmon Salmo salar smolts tagged with acoustic transmitters. Issue 3 (28th June 2016) - Newton, M.; Barry, J.; Dodd, J. A.; Lucas, M. C.; Boylan, P.; Adams, C. E.
Abstract : Mortality rates of wild Atlantic salmon Salmo salar smolts implanted with acoustic transmitters were assessed to determine if mortality was size dependent. The routinely accepted, but widely debated, '2% transmitter mass: body mass' rule in biotelemetry was tested by extending the transmitter burden up to 12·7% of body mass in small [mean fork length ( L F ) 138·3 mm, range 115–168 mm] downstream migrating S. salar smolts. Over the short timescale of emigration (range 11·9–44·5 days) through the lower river and estuary, mortality was not related to S. salar size, nor was a relationship found between mortality probability and transmitter mass: body mass or transmitter length: L F ratios. This study provides further evidence that smolt migration studies can deviate from the '2% rule' of thumb, to more appropriate study‐specific measures, which enables the use of fishes representative of the body size in natural populations without undue effects.